If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 290 + 10x = 625 Solving 290 + 10x = 625 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-290' to each side of the equation. 290 + -290 + 10x = 625 + -290 Combine like terms: 290 + -290 = 0 0 + 10x = 625 + -290 10x = 625 + -290 Combine like terms: 625 + -290 = 335 10x = 335 Divide each side by '10'. x = 33.5 Simplifying x = 33.5
| 2x+6+3+7x= | | (2w-5)+2w=32 | | 7x+15-9x=20-19x+17x-5 | | 11x-1=-9x-10 | | v+341/7=9 | | -3v-7/2=2/5v-3/2 | | 29.75+(.15m)=19.95+(.29m) | | 5x+15=8x-16 | | -6v+8=v+10-7v | | 4(a-7)+6(a-23)=14 | | 3x(x-6)=x+9 | | 18x-(6x-2)=62 | | -4r-2r+5= | | K+6+9= | | 27x+10=29 | | -3z-z= | | 5(b-96)+4=14 | | 0.1x-0.006=0.08+0.134 | | 64x^2-36y^2-512x-216y+124=0 | | y-(-3y)= | | 290+10(-29+0.1x)=y | | -4+n+7+4n=3-3n | | -88=-22b | | (4x-5)*(5x+6)= | | -6=18x | | 0=x^2+2x-1 | | 2x+5x+12=180 | | 6w-6=9w+5 | | 5y-42=18+y | | ((-3)-(6)+2)x(-1)= | | -8=20x | | (2x^5)/(98a^6*7a^2x) |